Development of the domestic meat and meat products market: problems and priorities - Strashynska, Larysa; Sheremet, Oleg (My University, 2021)
The article examines the domestic market of meat and meat products in terms of major development trends. Based on the balance of meat and meat products, the indicators of production, exports and imports are analyzed. The raw material base of the industry, where the leading position is occupied by poultry, which will continue to be the basis of the meat diet of the average Ukrainian, has been studied. It is proved that the domestic market of meat and meat products is characterized by weak consolidation of major producers, a high level of competition and significant diversification. The main market players are analyzed, each of which, producing the entire range of products, occupies a leading position in various product groups. It is proved that during the crisis the most successful were those producers who before the crisis began to form a vertically integrated chain - from raising livestock to the sale of finished products. The fund of consumption of meat and meat products per capita per year by regions was analyzed and the most priority areas were identified. The main trends and factors influencing the level of consumption are analyzed, the most important of which were the level of meat and meat products production and the ratio of prices and purchasing power of the population. The economic situation in the country and the seasonality of production also have a significant impact. Trends in the naturalization of food have influenced the development of the market by increasing demand for expensive meat products and chilled meat products. It was found that the demand for other products depends on the price and freshness of products. The main strategic goals and objectives for the development of the domestic market of meat and meat products are substantiated. Given that the production of meat and meat products is one of the most important and priority areas of the food market, it is emphasized that the importance of the meat processing industry lies in the balanced and interconnected functioning of different subsystems, namely production, processing and sale of meat products, meeting the needs of the population in meat and products of its processing. У статті досліджується вітчизняний ринок м’яса і м’ясопродуктів з точки зору основних тенденцій розвитку. На основі балансу м’яса та м’ясних продуктів проаналізовано показники виробництва, експорту та імпорту. Досліджено сировинну базу галузі, де лідируюче положення займає птиця, яка й у майбутньому складатиме основу м’ясного раціону пересічного українця. Доведено, що вітчизняний ринок м'яса та м'ясних продуктів відрізняється слабкою консолідацією основних товаровиробників, високим рівнем конкуренції та значною диверсифікацією. Проаналізовано основних гравців ринку, кожен з яких, вироблюючи весь асортимент виробів, займає лідируючі позиції за різними групами товарів. Доведено, що в період кризи найбільш успішними виявилися ті виробники, які ще до кризи почали формувати вертикально інтегрований ланцюг – від вирощування худоби до реалізації готових виробів. Проаналізовано фонд споживання м’яса та м’ясних продуктів в розрахунку на одну особу за рік по областях й визначені найбільш пріоритетні області. Проаналізовані основні тенденції та чинники, які впливають на рівень споживання, найвагомішими з яких виявилися рівень виробництва м'яса і м’ясопродуктів й співвідношення рівня цін та купівельної спроможності населення. Також значний вплив здійснює економічна ситуація в країні та сезонність виробництва. Тенденції до натуралізації продуктів харчування вплинули на розвиток ринку зростанням попиту на дорогу м'ясну продукцію й охолоджені м'ясні напівфабрикати. З'ясовано, що попит на іншу продукцію залежить від ціни та свіжості продукції. Обґрунтовано основні стратегічні цілі та завдання щодо розвитку вітчизняного ринку м'яса та м'ясних продуктів. Зважаючи на те, що виробництво м'яса і м'ясних продуктів є одним з найважливіших і пріоритетніших напрямів продовольчого ринку, наголошено, що значимість м’ясопереробної галузі полягає у збалансованому та взаємопов'язаному функціонуванні різних підсистем, а саме виробництва, переробки та реалізації м'ясної продукції, забезпечуючи потреби населення в м'ясі та продуктах його переробки.
Keywords: кафедра маркетингу; meat and meat products market; raw material base; consumer demand; production; level of consumption; meat processing industry; ринок м’яса та м’ясопродуктів; сировинна база; споживчий попит; виробництво; рівень споживання; м’ясопереробна галузь